2011
DOI: 10.1016/j.ijimpeng.2011.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic performance of multi-layered metallic plates impacted by a 7.62-mm APM2 projectile

Abstract: This paper presents a numerical investigation of the ballistic performance of monolithic, double-and triple-layered metallic plates made of either steel or aluminium or a combination of these materials, impacted by a 7.62-mm APM2 projectile in the velocity range of 775-950 m/s. Numerical models were developed using the explicit finite element code LS-DYNA. It was found that monolithic plates have a better ballistic performance than that of multi-layered plates made of the same material. This effect diminishes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
85
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(98 citation statements)
references
References 23 publications
10
85
0
3
Order By: Relevance
“…6b). This brittle behaviour has been reported in other numerical simulations [28] and experimental results [15] of bulk plate of AA 7075. It can be seen in Fig.…”
Section: Ballistic Performancesupporting
confidence: 85%
See 1 more Smart Citation
“…6b). This brittle behaviour has been reported in other numerical simulations [28] and experimental results [15] of bulk plate of AA 7075. It can be seen in Fig.…”
Section: Ballistic Performancesupporting
confidence: 85%
“…The JC material model has been successfully employed to model ballistic impact on (a) (b) aluminium plates [15,24,[26][27][28][29] and the parameters used in our model are reported in Table 1 and were validated against independent experimental observations of aluminium plates. Materials parameters for JC material model in Table 1 were obtained from [15], while damage parameters for the JC fracture criterion were obtained from [16,17].…”
Section: Validation Of the Jc Materials Model And Materials Parametersmentioning
confidence: 99%
“…They found that double layering of the target increased the ballistic limit velocity for spaced plates by nearly 40% compared to a monolithic target of equal thickness. In contrast, based on numerical investigation of monolithic, double-and triple-layered plates Flores-Johnson et al [13] concluded that monolithic plates had a better ballistic performance than a layered target. Multi-layered structures in different combinations were also considered in research conducted by Deng et al [14].…”
Section: Introductionmentioning
confidence: 98%
“…It has been observed that aluminium has some weaknesses compared to high-strength steel when dealing with structural impact. Since aluminium plates have poor ballistic performance, they are often utilised in multi-layered or spaced structures in combination with other materials [6,7].…”
Section: Introductionmentioning
confidence: 99%